Power, plain English, and the rise of modern poetry - Rosen, David, 1971- (Yale University Press, 2006)
This account of modern poetry presents a revisionist view of its' relation to Romanticism. As British poets from Wordsworth to Auden strived to present themselves both as persons of power and moral voices in their communities the rifts between plain English and their own ambitions became more difficult to reconcil.